2019
DOI: 10.1007/s00167-019-05447-w
|View full text |Cite
|
Sign up to set email alerts
|

Isolated medial patellofemoral ligament reconstruction significantly improved quality of life in patients with recurrent patella dislocation

Abstract: Purpose The purpose of this study was to measure the improvement in quality of life (QoL) following isolated anatomical double-bundle medial patellofemoral ligament reconstruction. Methods This is a single-centre, prospective study of 56 consecutive patients (57 knees) who underwent isolated MPFL reconstruction between 2014 and 2017. Functional outcome and QoL were assessed with the Kujala score and the EQ-5D-3L questionnaire, respectively. Objective outcomes were obtained through clinical examination at the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
(47 reference statements)
2
31
2
Order By: Relevance
“…It must be noted, however, that QoL includes multidimensional aspects and can be affected by the patient’s emotional and physical health, functional ability, and social environment [ 17 ]. Other studies assessed QoL after isolated MPFL-R with the EQ-5D-3L score [ 4 , 5 ]. After a comparable follow-up period, Biesert et al described a mean EQ-5D-3L VAS of 70 and an EQ-5D-3L Index of 0.78 in a Swedish cohort [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted, however, that QoL includes multidimensional aspects and can be affected by the patient’s emotional and physical health, functional ability, and social environment [ 17 ]. Other studies assessed QoL after isolated MPFL-R with the EQ-5D-3L score [ 4 , 5 ]. After a comparable follow-up period, Biesert et al described a mean EQ-5D-3L VAS of 70 and an EQ-5D-3L Index of 0.78 in a Swedish cohort [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, research on PFI has mainly focused on functional outcomes [ 1 , 4 , 13 , 14 , 24 , 26 , 35 , 44 ], re-dislocation rates [ 10 , 12 , 15 , 18 , 43 ], and return to sports [ 30 , 36 , 45 ]. Recently, research concerning Quality of Life (QoL) after MPFL-R has gained more attention [ 4 , 5 , 17 , 19 , 21 , 22 ]. Patient-reported QoL outcome measures are commonly seen as multi-dimensional and can therefore be influenced through a range of domains [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…27 MPFLR has become the most practical means for treating knee instability, and it has been frequently used for its ideal outcomes and relatively low rate of complications. 30 The majority of researchers have concluded that MPFLR alone could achieve reliable outcomes even in patients with bony deformity, 2,3,8,9,13,18,39 while others believe that it may be insufficient with isolated soft tissue surgery. 1,14,34 However, no consensus has been reached concerning when a concomitant bony procedure should be added to strengthen the MPFLR.…”
mentioning
confidence: 99%
“…Over the past decade, medial patellofemoral ligament (MPFL) reconstruction (MPFL-R) has been considered the most effective treatment for recurrent patellar dislocation (RPD), with a low redislocation rate. 1,2,10,13,19 However, because of the structural complexities of this disorder, unfavorable clinical outcomes after MPFL-R have also been reported recently. 23 It has been reported that isolated MPFL-R does not considerably improve patellar tracking or restore patellofemoral kinematics.…”
mentioning
confidence: 99%